Resposta metabólica de pacientes cirróticos (Child A) ao aumento da ingestão protéica e/ou calórica. Estudo do balanço nitrogenado. - Dichi, J. B.; Dichi, I.; Papini-Berto, S. J.; Bicudo, M. H.; Angeleli, A. Y.; Rezende, T. A.; Burini, Roberto Carlos [UNESP] (My University, 1992)
The dietary protein assimilation by cirrhotic undernourished patients (lower lean body mass and plasma TBPA and RBP levels) was investigated in five-adult male subjects suffering from histologically diagnosed liver cirrhosis, in its clinically mild stage (Child-Turcotte-Pugh grade A). During the 9 day-dietary study the patients received orally a sequence of complete-regional diets containing different protein-energy compositions identified as (g prot/Cal/kg/day): D0 = 0.42/20.9; D1 = 0.91/37.5; D2 = 0.99/47.9 and D3 = 1.60/40.5. The respective N-balance values (g/day) found were (mean +/- SD): low protein calorie (D0) = -4.24 +/- 2.46; normal protein calorie (D1) = 0.66 +/- 1.99; normal protein-high calorie (D2) = 1.14 +/- 2.54; high protein normal calorie (D3) = 5.12 +/- 2.48. The correspondent urea-N output (g/kg/day) were D0 = 0.22 +/- 0.100; D1 = 0.238 +/- 0.099; D = 0.20 +/- 0.063 and D3 = 0.310 +/- 0.121. The present data thus suggest that protein rather than energy intake would be the limited factor for increasing the N-retention in (mild) cirrhotic patients whom tolerate well dietary protein at either normal or elevated levels.
Metabolic response of cirrhotic patients (Child A) to the increase of protein and/or caloric intake. Nitrogen balance study
Keywords: nitrogen; adult; body mass; diet therapy; epidemiology; human; liver cirrhosis; male; metabolism; nutritional status; protein intake; Adult; Body Mass Index; Dietary Proteins; English Abstract; Human; Liver Cirrhosis; Male; Middle Age; Nitrogen; Nutritional Status; Sampling Studies